Qurʾānic Mushrikūn Between Monotheism and Idolatry - Muhammed Coşkun (Kocatepe İslami İlimler Dergisi)
This article critically examines the two central claims made by G.R. Hawting in The Idea of Idolatry and the Emergence of Islam. Hawting argues that the Qur’ānic term mushrik (polytheist) has been misinterpreted in classical Islamic tradition and is entirely understood as referring to "idol worship." He contends that the Qur’ān actually critiques defective monotheistic practices with this term, using mushrik as a polemical device. Based on this, Hawting questions the origins of the Qur’ān, asserting that its addressees were not "polytheistic," and thus it is impossible for the Qur’ān to have originated from the pagan Arabs of the Hijaz. In this context, Hawting suggests that the Qur’ān was influenced by the broader religious environment of the late antiquity and emerged in the Fertile Crescent, a region where various religious groups accused each other of being mushrik.This article aims to provide a comprehensive critique of these two central claims by Hawting. This chapter begins by examining the concept of mushrik in the Qur’ān and its interpretation within Islamic tradition, focusing on how classical exegesis framed this term within historical and theological contexts. Following this, the article discusses the religious and cultural milieu of pre-Islamic Arabia, drawing on archeological and epigraphic evidence to articulate Hawting’s hypothesis. The article reveals that pre-Islamic Arab society was not entirely polytheistic. Rather, this society had a belief system that recognized Allah as the supreme creator, relying on intermediaries to approach Him. Furthermore, the article shows that contrary to Hawting’s argument, classical Muslim scholars have recognized this aspect significantly. According to the conclusions reached, while Hawting’s critique of the literal interpretation of mushrik is reasonable and valid, his other claims based on this conclusion are not scientifically grounded and reflect the baggage of revisionist Orientalism. This article aims to provide a comprehensive critique of these two central claims by Hawting. This chapter begins by examining the concept of mushrik in the Qur’ān and its interpretation within Islamic tradition, focusing on how classical exegesis framed this term within historical and theological contexts. Following this, the article discusses the religious and cultural milieu of pre-Islamic Arabia, drawing on archeological and epigraphic evidence to articulate Hawting’s hypothesis. The article reveals that pre-Islamic Arab society was not entirely polytheistic. Rather, this society had a belief system that recognized Allah as the supreme creator, relying on intermediaries to approach Him. Furthermore, the article shows that contrary to Hawting’s argument, classical Muslim scholars have recognized this aspect significantly. According to the conclusions reached, while Hawting’s critique of the literal interpretation of mushrik is reasonable and valid, his other claims based on this conclusion are not scientifically grounded and reflect the baggage of revisionist Orientalism.